(untitled) (Alternautas, 2022)
Mexico, production of urban space, violence and dispossession, capital accumulation, David Harvey Mexico seems to be immersed in an unending series of catastrophes. Every day new stories of injustices and horrible deaths smother us. Social networks, both physical and virtual, are continuously filled with outrage, which more often than not, suddenly decays. This processes, some clearly connected and others apparently distant, can be explained in a systematic fashion through the work of David Harvey. In his work, Harvey has sought to explain how capital accumulation produces and transforms space. This focus has established his body of work as one of the main contributions to Marxist theory in the last fifty years. In particular, he has focused on explaining the production of urban space; the role of violence and dispossession in the accumulation of capital, and the role finance plays in the capitalist system and its crises. Even if these three topics were scarcely explored by Marx, Harvey looks for clues and follows his steps in a critical and complementary way.